Etiologies and Impact of Readmission Rates in the First 180 Days After Hematopoietic Stem Cell Transplantation in Children, Adolescents, and Young Adults. Issue 8 (November 2017) - Maher, Ossama M.; Silva, Jorge G.; Huh, Winston W.; Cuglievan, Branko; DePombo, April; Kebriaei, Partow; Park, Minjeong; Liu, Diane; Tillman, Chloe; Tarek, Nidale; Cooper, Laurence J.N.; Tewari, Priti
Abstract : Introduction: High rates of patients require readmission to the hospital within 6 months of hematopoietic stem cell transplantation (HSCT). We investigated the relationship between readmission rates and outcomes after HSCT in children, adolescents, and young adults (CAYA). Materials and Methods: A retrospective analysis of patients (26 years or younger) treated with HSCT was conducted. Results: A chart review of 435 CAYA who underwent HSCT from 2008 to 2015 revealed that 171 patients (39%) had at least 1 hospital readmission within 180 days of transplant; 87% received allogeneic and 13% received autologous HSCT. A total of 312 readmission events were reported. The median follow-up time was 31 months. Documented infection (n=99) and graft-versus-host disease complications (n=60) were the most common causes. Higher than 2 readmission rates were associated with lower overall survival (OS) ( P =0.001) and disease-free survival ( P <0.001) in patients who received allogeneic HSCT. These findings were not found in the autologous HSCT. In a multivariate analysis of those who received allogeneic HSCT, prior treatment with ≥2 chemotherapy regimens ( P =0.03) was independent predictor of lower OS. There were also trends noted toward lower OS for patients with documented infections at index admission or subsequent readmissions ( P =0.09). Conclusions: More than 2 hospital readmissions within 6 months of allogeneic HSCT in CAYA, who are either heavily pretreated or had documented infections at index admission or subsequent readmissions adversely affected the outcomes.